Effect of solution treatment temperature on microstructure and mechanical properties of a356 alloy - Muhamad Azrul, Amir (2012)
Aluminum content in a vehicle is keep increasing around the globe due to the needs to reduce vehicle weight and increase fuel efficiency. The majority of the components are cast product which mostly casted from A356 alloy because of its excellent characteristics such as cast ability, high weight-to-strength ratio, good corrosion resistance and good weld ability compared to other types of alloy. Heat treatment is done to harness the full potential of cast A356 alloy and T6 is the commonly used heat treatment for this alloy. Most of the solution treatments (ST) study is done on sample having α-Al with dendritic structure. The specimen was cast using low pouring temperature (LPT) method which produces equiaxed α-Al structure. The objective of this research is to study the effect of ST temperature on microstructure and mechanical properties of A356 (Al7Si0.3Mg) aluminum alloy. The specimen undergone ST for two (2) hours at three different temperatures (530 °C, 540 °C, and 550 °C), quenched in water at room temperature, and artificial aged for six (6) hours at 170 °C. Mechanical properties of A356 aluminum alloy were investigated by utilizing tensile test and hardness test, the later is the main interest of this study. The relation between size, shape, and distribution of Si particle and the alloy’s mechanical properties were investigated. It was found that Si particle size, shape, and dispersion affect the mechanical properties of cast A356 alloy. Higher ST temperature produce smaller and more globular Si particle before completing T6 heat treatment. Elongation decreases while ultimate tensile strength (UTS) increased as ST temperature increased from 530 °C to 550 °C. A356 aluminum alloy specimen solution treated at 530 °C have comparable hardness compared with specimen ST at 540 °C before and after artificial ageing (AA) - complete T6 heat treatment - with higher elongation and lower energy usage as added benefit.